Peningkatan Pendidikan Kebaharian Melalui Program Sekolah Pantai Indonesia - Erni Mulyanie; Hadyan Nur Fadilah (Kilau Publishing, 2024)
Indonesia has a very large coastal and marine area and every year it experiences physical damage, one of which is due to marine pollution. Indonesia is capable of producing up to 187.2 million tons/year of waste. Implementing maritime education in the education curriculum in Indonesia is the right step to reduce pollution. Since 2017, the Indonesian Beach School Program (SPI) initiated by the Ministry of Maritime Affairs and Fisheries has been implemented to realize maritime education in Indonesia. The problem in this research is how to implement the Indonesian Beach School Program (SPI) in an effort to improve maritime education at Mitra Maritime Vocational School, Indramayu Regency. The method used in the research is a descriptive method with a quantitative approach. The research location was carried out at Mitra Maritim Vocational School, Indramayu Regency. Based on the research results, it was found that the implementation of the Indonesian Beach School Program is an effort to improve marine education through observing mangrove ecosystems and their management, beach dynamics, marine pollution and distribution of weather, climate and climate change information. Based on the results of this research, it can be concluded that the implementation of the Indonesian Beach School Program (SPI) at Mitra Maritime Vocational School, Indramayu Regency has been carried out well, various agencies/institutions help and support the implementation of the Indonesian Beach School Program (SPI).